2022
DOI: 10.21608/mjppf.2022.272864
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Control of Grassy Weeds in Drill-Seeded Rice (Oryza Sativa L.)

Abstract: Weeds are the main obstruction under drill-seeded rice system so that two field experiments were conducted at the experimental farm of Rice Research & Training Center, Sakha Agricultural Research Station, Kafrelsheikh, Egypt in the summer seasons of 2020 and 2021 to reset the best chemical control program against grassy weeds in drill-seeded rice (Giza 179 cv.). Randomized Complete Block Design (RCBD) with three replications was used during both seasons of study. Ten chemical weed control were applied; (1) pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…The considerable increase of rice growth and yield and its components in case of using sequential application of Saturn followed by Nominee 2% + Inpul 75% reflex the high efficiency of such treatment in controlling weeds and enhancing more favorable conditions of moisture, nutrients, sun light and space for rice crop. These results are in harmony with those found by Abd El-Naby et al [40] and Abd El-Naby and El-Ghandor [16].…”
Section: Weed Control Effectsupporting
confidence: 92%
See 4 more Smart Citations
“…The considerable increase of rice growth and yield and its components in case of using sequential application of Saturn followed by Nominee 2% + Inpul 75% reflex the high efficiency of such treatment in controlling weeds and enhancing more favorable conditions of moisture, nutrients, sun light and space for rice crop. These results are in harmony with those found by Abd El-Naby et al [40] and Abd El-Naby and El-Ghandor [16].…”
Section: Weed Control Effectsupporting
confidence: 92%
“…Singh et al, [31] 2016 found that sequential application of pendimethalin as preemergence herbicide followed by postemergence application of bispyribac-sodium surpassed the application of pre or postemergence herbicides alone in weed control. These results are in harmony with those obtained by Abd El-Naby and El-Ghandor [16].…”
Section: Effect Of Weed Controlsupporting
confidence: 91%
See 3 more Smart Citations